Exploration of Chinese Novice Teachers' Teaching Practices and Questioning in Teaching English Reading Classes - Hang, Sha; Chayanuvat, Anchalee (International Journal of Multidisciplinary in Management and Tourism, 2024)
This article aimed to study (1) explore Chinese novice English teachers' teaching practices in English reading comprehension classes (2) analyze the types of questions used by Chinese novice English teachers in English reading comprehension classes, the sample was five novice teachers from Yunnan Province, China. They were selected by purposive sampling method from the research population of 22 teachers. the instrument for collecting data was classroom observation checklists of 10 lessons of, 5 lesson plans and 5 teacher journals. Analysis data by Descriptive statistics and Content Analysis. The research results were found as follows; 1. In teaching practices, Chinese novice English teachers clearly communicated their teaching objectives, effectively focused on reading content, teaching resources, and had strong reflective abilities. However, deficiencies were found in diversifying teaching methods, teacher-student interaction, extended and independent learning. 2. Chinese novice English teachers used a high proportion of low-level cognitive questions (PCT=76%) and a lack of attention to high-level cognitive questions (PCT=34%). The PCT of each cognitive level was: Remember (40%); Understand (31%); Analyze (11%); Evaluate (10%); Apply (5%); Create (3%).